RehabilitacjaApplication of bi-level positive airway pressure ventilation during early therapy of patients after heart surgery - Piwoda, Agnieszka; Potępa, Łukasz; Ziętkiewicz, Mirosław; Sadowski, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
The aim of this paper is to present the BiPAP Vision device, which supports breathing non-invasively during the early period of respiratory physiotherapy in patients after cardiac surgery. This device is still largely unknown and rarely used in Polish medicine. Apart from discussing the concept of the instrument’s functioning as well as the advantages and disadvantages of its application, the authors attempt to present the usefulness of the BiPAP Vision device during therapy after heart surgery. Over a period of four months, twenty patients with respiratory failure early (up to two days) after extubation preceded by cardio surgical procedure (coronary bypass surgery, implantation of heart valves or valvuloplasty, correction of heart failure – atrial septal defect or ventricular septal defect) were observed. The study population was divided into two groups. The general criterion was the time when pulmonary insufficiency symptoms occurred. That required the application of the BiPAP Vision device. In this article, the authors also present BiPAP Vision parameters which were used during non-invasive therapy, i.e.: inspiratory positive airway pressure – IPAP (mean in both groups: 14 cmH2O), expiratory positive airway pressure – EPAP (mean in both groups: 8 cmH2O), fraction of inspired oxygen – % 02 (40-50%). Data analysis in examination groups demonstrated that using the equipment for non-invasive ventilation of the BiPAP Vision type is a more effective and better tolerated form of prevention of re-intubation among patients after heart surgery with respiratory failure. Modifying the physiotherapeutic methods applied during the treatment of such patients using non-invasive ventilation increases the efficiency and effectiveness of therapeutic activities.